DEVELOPMENT OF TEACHING MATERIALS OF TEMBUNG (UPDATE CONTINUOUS) IN CLASS I ELEMENTARY SCHOOL - Urip Umayah (Universitas PGRI Yogyakarta, 2022)
Curriculum writing is one of the language skills that must be mastered by lower grade elementary school students in accordance with the competency standards demanded by the curriculum. In fact, there are still many students who have not mastered the skill of writing tembung (upright cursive) because some students write with tembung which is very complicated, so that only a few skilled students are able to achieve the KKM. The development of tebung teaching materials is an alternative to improve the writing skills of elementary school students. The purpose of this study is